Changes Over Time in Post-traumatic Stress Disorder Among Children Who Survived the 2008 Wenchuan Earthquake and Predictive Variables - Chen, Ying; Lam, Chow; Deng, Hong; Ko, Kam Ying (Frontiers in Psychiatry, 2021)
Background: This study examines changes over time in posttraumatic stress disorder (PTSD) among children who survived the 2008 Wenchuan earthquake and the relevant predictive variables. Methods: A total of 203 children and adolescents were investigated 24 months after the earthquake, and 151 children and adolescents completed the one-year follow-up study. Participants completed the Children’s Revised Impact of Event Scale (CRIES-13), the Center for Epidemiologic Studies Depression Scale (CES-D) and the Connor-Davidson Resilience Scale (CD-RISC). Hierarchical linear regression analysis was used to evaluate the predictors of changes in PTSD severity. Results: Eighty percent of the children still had some PTSD symptoms 2 years after the Wenchuan earthquake, and 66.25% of the children had symptoms that lasted 3 years. In the model predicting PTSD symptom severity, the loss of family members and child burial explained a significant 21.9% of the variance, and depression explained a significant 16.7% of the variance. In the model predicting changes in PTSD severity, the change scores for resilience and depression explained a significant 18.7% of the variance, and cognitive behavioural therapy (CBT) explained a significant 33.6% of the variance. Conclusions: PTSD symptoms in children and adolescents can persist for many years after trauma. In addition to using psychological interventions to improve PTSD symptoms, improvements in depression and resilience should also be considered.